The Antibiotic Resistance Genes Contamination of Strawberries With the Long-Term Use of Raw, Aerobic Composting, and Anaerobic Composting Livestock Manure: A Comparative Study - Zhang, Wei-Guo; Zhang, Ming-Sha; Li, Wen (Frontiers in Environmental Science, 2022)
Strawberries are one of the most widely consumed fruits worldwide. In this study, we hypothesized the antibiotic resistance genes (ARGs) contamination of strawberries was alleviated by the long-term use of composting livestock manure in comparison with raw livestock manure. Our results suggested that compared with the long-term use of raw livestock manure, both the long-term use of aerobic and anaerobic composting livestock manure reduced the ARGs diversity and abundance of strawberries. The correlation analysis between ARGs and mobile genetic elements revealed the process of horizontal gene transfer of ARGs was attenuated when strawberries were fertilized with long-term use of composting livestock manure, especially the anaerobiotic composting manure. The phylum Proteobacteria, Firmicutes, and Myxococcota were identified as the potential ARGs hosts which exerted the vital role in the environmental behavior of ARGs via network co-occurrence analysis between antibiotic resistome and microbiome. Our findings highlighted that the contamination of ARGs of strawberries was alleviated by the long-term use of composting livestock manure, especially the anaerobiotic composting manure.